Priorização do transporte coletivo por ônibus em sistemas centralizados de controle de tráfego - Oliveira Neto, Francisco Moraes de (2004)
In the last years, bus priority techniques for signals controlled by urban traffic control (UTC) systems have become a viable alternative to reduce passengers delays at signalized intersections, especially in mixed traffic corridors. However, before deploying any bus signal priority strategy in such corridors, the impacts should be evaluated on the different users of the system. This work had as its main objective to assess the operational performance of passive and active bus priority techniques in fixed and real time signal systems at one of the main arterial corridors in Fortaleza. As a secondary objective, it also evaluated the operationalbenefits of SCOOT adaptive signal control system, comparing it to well adjusted fixed time plans optimized by TRANSYT, for periods of medium and high traffic volumes.In evaluating alternative scenarios, the following performance measures were considered: vehicle delay and number of stops simulated by SCOOT, as well as buses and autos travel times observed in the field during each scenario's operation. The results did not favor the adoption of passive and active priority schemes in the studied corridor, leading to the conclusion that SCOOT's real time control, programmed for a good signal progression of the general traffic (buses and autos), is the best signal control strategy for an arterial corridor with similar characteristics as the one under analysis. The reasons for negative impacts in the operational performance of the passive priority strategies were related to higher interaction between buses and cars, and also to the significant variability in dwell times at bus stops along the corridor. The low performance of the active priority strategies in real time signal operation was due to the loss in signal progression with traffic disruptions caused by SCOOT active priority model.